FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN TIMELINESS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Empiris Perusahaan Consumer Goods Tahun 2007-2010) - Ilmiah, Ridha; Pusposari, Devi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The objectives of this research is to find out empirical evidence of firm size, profitability, internal auditor, public accountant firm size, and solvability affect toward audit delay and timeliness. The sample of population of this study was listed consumer goods companies at the Indonesian Stock Exchange (ISX). There were 100 sample companies meeting the criteria for 2007-2010 periods. Sampling selection by purposive sampling method. This result of this research by using multiple regression analysis method show that firm size, internal auditor, and public accountant firm size are able to affect audit delay partially, whereas by using logistic regression analysis method the result show that only internal auditor are able affect timeliness partially. Â Keywords: Audit delay, timeliness, firm size, profitability, internal auditor, public accountant firm size, and solvability.